2000
DOI: 10.1007/s004390000364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular definition of Xq common-deleted region in patients affected by premature ovarian failure

Abstract: High-resolution cytogenetic analysis of a large number of women with premature ovarian failure (POF) identified six patients carrying different Xq chromosome rearrangements. The patients (one familial and five sporadic cases) were negative for Turner's stigmata and experienced a variable onset of menopause. Microsatellite analysis and fluorescent in situ hybridization (FISH) were used to define the origin and precise extension of the Xq anomalies. All of the patients had a Xq chromosome deletion as the common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 30 publications
7
67
0
3
Order By: Relevance
“…Results from the investigation of X-autosome balanced translocations and Xq terminal deletions suggest the presence of two loci on Xq (POF1, located at Xq26-q28; and POF2, located at Xq13.3-q22) that appear to be involved in ovarian function (Marozzi et al 2000). Microarray analysis for our patient demonstrated a loss of DNA copy number at the Xq subtelomeric region (Xq28), consistent with the POF1 critical region.…”
Section: Discussionsupporting
confidence: 61%
“…Results from the investigation of X-autosome balanced translocations and Xq terminal deletions suggest the presence of two loci on Xq (POF1, located at Xq26-q28; and POF2, located at Xq13.3-q22) that appear to be involved in ovarian function (Marozzi et al 2000). Microarray analysis for our patient demonstrated a loss of DNA copy number at the Xq subtelomeric region (Xq28), consistent with the POF1 critical region.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports have suggested different critical region on Xq arm to be associated with premature ovarian failure (POF) which involve Xq13.3-q22 [29] and Xq26-q28 [41]. Subsequent studies also suggested Xq26.2-q28 [21], Xq27.2/Xq27.3-Xq28 [8] and Xq13-21 and Xq23-28 [44] are the regions associated with POF (Fig. 4).…”
Section: Discussionmentioning
confidence: 93%
“…POF1 (Xq23q27 or Xq2628) region deletions are much more commonly related to POF, and the haploinsufficiency of those deleted genes that normally escape X inactivation may be harmful to ovarian function [9]. Marozzi et al [10] studied six POF patients with rearranged Xq chromosomes and revealed that the POF1 region extends from Xq26.2 to Xq28.…”
Section: Discussionmentioning
confidence: 99%